2022
DOI: 10.3389/fphar.2022.932874
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of total glucosides of paeony in the treatment of systemic lupus erythematosus: A systematic review and meta-analysis

Abstract: Background: Total glucosides of paeony (TGP), extracted from the Chinese medicine Paeonia lactiflora Pall., have been proven to be effective in various autoimmune diseases. We aim to systematically evaluate the efficacy and safety of TGP combined with different conventional therapeutic agents in the treatment of systemic lupus erythematosus (SLE).Methods: Eight databases were searched for randomized controlled studies of TGP for SLE. The search time was set from the establishment of the databases to March 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…[Ranunculaceae; Paeoniae Radix Alba]. It has good immunoregulatory effects and has been widely used in the treatment of autoimmune diseases such as rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and Sjogren's syndrome, demonstrating good safety (Jiang et al, 2020;Gong et al, 2022). Previous studies showed the possible mechanism of TGP in the treatment of RAU might include regulating inflammatory factors (TNF-α, IL-1β, IL-6, IL-12, TGF-β, and IL-10) (Shi et al, 2014;Giannetti et al, 2018;Zhao et al, 2018), balancing the ratio of CD4 +/CD8 + T cells (Sun et al, 2000) and Th1/Th17 cells (Kong et al, 2018), inhibiting the sensitivity of T cells to inflammation (Shi et al, 2014), and decreasing the secretion of secretory immunoglobulin A (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[Ranunculaceae; Paeoniae Radix Alba]. It has good immunoregulatory effects and has been widely used in the treatment of autoimmune diseases such as rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and Sjogren's syndrome, demonstrating good safety (Jiang et al, 2020;Gong et al, 2022). Previous studies showed the possible mechanism of TGP in the treatment of RAU might include regulating inflammatory factors (TNF-α, IL-1β, IL-6, IL-12, TGF-β, and IL-10) (Shi et al, 2014;Giannetti et al, 2018;Zhao et al, 2018), balancing the ratio of CD4 +/CD8 + T cells (Sun et al, 2000) and Th1/Th17 cells (Kong et al, 2018), inhibiting the sensitivity of T cells to inflammation (Shi et al, 2014), and decreasing the secretion of secretory immunoglobulin A (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It could reduce the disease activity of SLE and the incidence of adverse reactions. Moreover, TGP could improve other outcomes related to SLE disease activity, including complement proteins (C3 and C4), immunoglobulins (IgA, IgM and, IgG), ESR, CRP, 24 h urine protein, and recurrence rate [117].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…[Ranunculaceae; Paeoniae Radix Alba]. It possesses immunoregulatory properties and has been widely utilized in the treatment of autoimmune diseases ( Jiang et al, 2020 ; Gong et al, 2022 ). Based on the findings of several randomized controlled trial (RCT)-based meta-analyses ( Luo et al, 2017 ; Feng et al, 2019 ; Zheng et al, 2019 ; Wang et al, 2022 ; Yang et al, 2023 ), it is suggested that combining TGP with effective therapeutic drugs can lead to more significant treatment efficacy for Sjogren’s syndrome, systemic lupus erythematosus, psoriasis, and rheumatoid arthritis compared to using these drugs alone.…”
Section: Introductionmentioning
confidence: 99%